Penguatan Pendidikan Karakter Santri Melalui Pembelajaran Kitab Taklim Muta'alim di Pondok Pesantren Ulil Albab Ngawi - Sumarno; Widiyanto; Mudofir; Yusuf Rohmadi; Nemer Alotaibi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Character education is a primary focus in the development of the educational system at Pesantren Ulil Albab Ngawi. As an Islamic educational institution, it implements the learning of the Kitab Taklim Muta'alim as a means to strengthen the character education of its santri (students). This research aims to analyze how learning the Kitab Taklim Muta'alim can contribute to reinforcing character values. The research method used is descriptive qualitative with a case study approach, where data was obtained through interviews, observation, and documentation. The research results indicate that learning the Kitab Taklim Muta'alim not only teaches religious aspects but also shapes positive attitudes and behaviors such as politeness, humility, honesty, responsibility, and discipline among the pesantren community, which form the foundation of santri character. To further strengthen character education through the Kitab Taklim Muta'alim at Pesantren Ulil Albab Ngawi, recommendations include: developing teacher training programs, integrating experience-based learning, and establishing assessment and monitoring mechanisms.